The Association between The Degree of Liver Cirrhosis Severity and Zinc Serum Level - Budi Yuwono; Ummi Maimunah; Budi Widodo (Universitas Airlangga, 2020)
Background: Impaired liver function in LC (Liver Cirrhosis) can cause Zinc deficiency (Zn). One of the causes of Zn deficiency in LC is decreased albumin synthesis, whereas albumin is required as the main Zn binding protein in plasma. However, some studies of the severity of LC with Zn serum levels still provide controversial results.Objective: To determine the association between the degree of LC severity and Zn serum level.Methods: The subjects of this study were LC patients in Gastroentero-Hepatology Unit and Internal medicine wards in of Dr. Soetomo General Hospital Surabaya for three months. Diagnosis of LC was based on clinical examination according to Soehardjno-Soebandiri criteria and other findings (ultrasound or endoscopy). The degree of LC severity was determined based on the CTP score (Child-Turcotte-Pugh). Serum Zn concentration was measured by atomic absorption spectrophotometry method. The research design used the cross-sectional method. The statistical test used was Spearman correlation.Results: Forty-three patients fulfilled the study criteria. The subjects consisted of 27 males (62.8%) and 16 females (37.2%) with the mean age of 53.81 ± 8.67 years. Based on the CTP scores, we obtained CTP A of 4 patients (9.3%), CTP B of 19 patients (44.2%) and CTP C of 20 patients (46.5%). The mean of Zn serum level in CTP A, CTP B, and CTP C score was 58.3 ± 19.6 μg/dl, 43.4 ± 14.5 μg/dl and 31.6 ± 10 μg/dl respectively. The result of the statistical test showed a significant correlation between LC severity and Zn serum level (p <0.05 and r = -0.583).Conclusion: The heavier the severity of LC, the lower Zn serum levels.